Influence of added zinc from zinc sulfate on weanling pig growth performance and plasma zinc concentration - Woodworth, J.C.; O'Quinn, P.R.; Sawyer, J.T.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of288 weanling pigs (13.4lb and 18 d of age) was used in a 27 d growth assay to determine the effects of adding Zn from ZnS04 or ZnO on growth performance. Pigs were allotted to one of eight dietary treatments consisting of a control diet; diets containing one of six concentrations of Zn from ZnS04 (SOD, 1,000, 1,500,2,000,2,500, or 3,000 ppm); and a diet containing 3,000 ppm of Zn from ZnO. Increasing Zn from ZnS04 linearly improved ADO and FlO from d 9 to 19; however, adding ZnS04 to the diet decreased ADO from d 19 to 33. Thus, pigs fed diets containing ZnS04 or 3,000 ppm of Zn from ZnO had similar growth performance compared to pigs fed the control diet for the overall trial. In conclusion, no benefit was observed for the overall trial from adding increasing concentrations of Zn from ZnS04 or 3,000 ppm ofZn from ZnO.
Keywords: Swine; Early-weaned pigs; Growth; Zinc